Does functional diversity in interfirm collaborations lead to innovation diversity? Firm‐level evidence from the Australian food industry*. (6th June 2022) - Azeem, Muhammad Masood; Fazal‐e‐Hasan, Syed; Gutiérrez, Leopoldo; Baker, Derek
Abstract : Research on the collaboration–innovation nexus emphasises that collaborations and innovation are multidimensional. Despite this emphasis, there is limited evidence on how firms' collaborative diversity affects their innovation diversity. This paper addresses this gap by examining the relationships between (i) a firm's functional diversity of collaboration (FDC) and innovation diversity, and (ii) innovation diversity and firm growth. We used longitudinal data from 738 Australian food firms, and our findings suggest that the positive relationship between FDC and innovation diversity reaches a point of saturation, beyond which additional collaboration negatively influences firms' innovation diversity. Moreover, innovation diversity depends on the motives behind alliance formation and the firm's focus on innovation. Finally, the association between innovation diversity and growth performance is heterogeneous across firms' conditional growth rate distribution.